Sosialisasi Dampak Gadget Terhadap Perilaku Belajar Peserta Didik SD Negeri 1 Bugi - Wasalmi Wasalmi; Rosna Ode; Melan Sari; Tita Tita; Wulan Wulan (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The development of students has a significant impact on gadgets, whether psychologically, socially, or even physically. This can occur if gadget usage is performend inappropriately and excessively. Our socialization program is designed to illustrate the effect of gadgets on students’ learning behaviour at SD Negeri 1 Bugi. Tablets, smarthphones, and other gadgets that have become ubiquitous in our daily lives have come to be an integral part of our daily lives. However, the presence of gadgets in an educational setting can have a complex effect on students’ learning behaviours. Our method is based on the lecture method, where students are debriefed and videos and pictures are used to enhance their comprehension. Following our socializing, we carried out a pretest. And good changes were found where there wa s rise in students knowledge and understanding of gadgets by 90%. The implementation of this socialization is very important in this extraordinary era of the onslaught of gadgets because the use of gadgets has a significant impact on students’ learning behavior in some cases the excessive use of gadgets can interfere with students’ concentration and focus in learning. Gadgets can also serve as powerful tools to increase student engagement and motivation. Furthermore, the need for appropriate socialization concerning the use of gadgets in the educational context. Parents, teachers, and other relevant parties should understand and educate students on how to use gadgets safely and wisely.